2004
DOI: 10.1002/pssb.200301973
|View full text |Cite
|
Sign up to set email alerts
|

Time resolved photoluminescence study of Si modulation doped GaN/Al0.07Ga0.93N multiple quantum wells

Abstract: The effects of the Si doping level on the recombination dynamics and carrier (exciton) localization in modulation doped GaN/Al 0.07 Ga 0.93 N multiple-quantum-well (MQW) structures were studied by means of photoluminescence (PL) and time-resolved PL measurements. All samples with different doping levels show a QW emission which is blue shifted with respect to the 3.48 eV PL peak from the GaN buffer layer. The decay time at the peak position remains nearly constant in the range of 320-420 ps at 2 K for all dopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…1). Time-resolved PL measurements [7] have revealed that the decay time is nearly independent on the emission energy and has a value of 350-400 ps in all doped samples. This is quite surprising for modulation doped QWs and could only be explained if localized holes are involved in the optical transitions.…”
Section: -9×10mentioning
confidence: 98%
See 1 more Smart Citation
“…1). Time-resolved PL measurements [7] have revealed that the decay time is nearly independent on the emission energy and has a value of 350-400 ps in all doped samples. This is quite surprising for modulation doped QWs and could only be explained if localized holes are involved in the optical transitions.…”
Section: -9×10mentioning
confidence: 98%
“…Moreover, a degenerate two-dimensional (2D) electron gas is formed in the wells and many-body effects have to be considered in the analysis of the recombination mechanism. Recently, we have studied in detail the low-temperature emission in shallow GaN/AlGaN multiple quantum wells (MQWs) with heavily Si-doped barriers [6,7]. An asymmetrical emission lineshape with the peak energy exhibiting a nonmonotonic dependence on the doping density has been observed.…”
Section: Introductionmentioning
confidence: 97%
“…42,43 In general, Si doping improves the radiative efficiency due to screening of the well-width fluctuations and partial compensation of the electric field. 40,44,45 In this work we first analyze the structural quality of GaN / AlGaN MQW structures grown by PAMBE under different conditions. The sample structure was designed for ISB transitions in the mid-infrared, i.e., below the LO-phonon energy.…”
Section: Introductionmentioning
confidence: 99%
“…These polarization charges create internal fields in the QWs of the order of MV/cm which have fundamental influence on the optical properties and strongly affecting the oscillator strengths of excitons as well as the spectral position of the correspon− ding photoluminescence (PL) peaks. A huge redshift of the transition energy and a strong increase in the carrier lifetime due to the quantum confined Stark effect are marked fea− tures in the optical spectra of GaN/AlGaN quantum wells, extensively debated in many publications [9,10].…”
Section: Introductionmentioning
confidence: 99%